2021
DOI: 10.3389/fimmu.2021.699386
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Biomarkers of NETosis in the Serum of Pediatric Patients With Type 1 Diabetes and Their First-Degree Relatives

Abstract: Type 1 diabetes (T1D) is an autoimmune disorder with unambiguous involvement of both innate and adaptive immune mechanisms in the destruction of pancreatic beta cells. Recent evidence demonstrated that neutrophils infiltrate the pancreas prior to disease onset and therein extrude neutrophil extracellular traps (NETs), web-like structures of DNA and nuclear proteins with a strong pro-inflammatory biologic activity. Our previous work showed that T1D NETs activate dendritic cells, which consequently induce IFNγ-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In adult autoantibody-positive and newly diagnosed T1D individuals, serum levels of MPO and NE were shown to be increased, suggesting enhanced NETosis [ 18 ]. This was also the case in the pediatric population, where increased levels of MPO and NE, as well as other NET-associated biomarkers such as PR3, PAD4, cell-free DNA-histone complexes, and extracellular DNA were observed at the time of T1D onset [ 19 , 20 ]. However, other studies have reported lower MPO-DNA markers as well as reduced NE and PR3 levels in adults with established T1D compared to healthy control (HC) donors [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In adult autoantibody-positive and newly diagnosed T1D individuals, serum levels of MPO and NE were shown to be increased, suggesting enhanced NETosis [ 18 ]. This was also the case in the pediatric population, where increased levels of MPO and NE, as well as other NET-associated biomarkers such as PR3, PAD4, cell-free DNA-histone complexes, and extracellular DNA were observed at the time of T1D onset [ 19 , 20 ]. However, other studies have reported lower MPO-DNA markers as well as reduced NE and PR3 levels in adults with established T1D compared to healthy control (HC) donors [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 90%
“…As such, the various T1D stages might have an impact on the reported NETosis levels in the aforementioned studies. As for the techniques used to determine levels of NETosis, the studies described either indirect measurements of NET formation (i.e., serum or plasma levels of NET markers such as MPO and NE or extracellular DNA) or employed error-prone, laborious, and relatively subjective methods to measure NETosis levels (i.e., manual counting) [ 18 , 19 , 20 , 21 , 22 ]. It could be argued that these discrepancies might affect the reported NETosis levels.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of neutrophils and biomarkers of NETosis, including neutrophil elastase and cfDNA, were elevated in the serum of pediatric patients with recent‐onset T1D, suggesting that altered neutrophil activity leading to increased NETosis at disease onset may be involved in the inflammatory trigger of T1D. 60 In fact, inhibition of peptidylarginine deiminases 4, primarily expressed in neutrophils and critical in the NETs generation, by cl‐amidine decreased T1D incidence and delayed its onset in nonobese diabetic mice. 61 Furthermore, proteomic characteristics, determined by gene ontology analysis, of plasma microparticles from patients with T2D showed that levels of S100A8/A9 were upregulated 26 (Table 1 ).…”
Section: Platelet/neutrophil Alterations As Potential Drivers For Dia...mentioning
confidence: 99%
“…Type 1 diabetes (T1D), closely related to islets in pancreas, is an autoimmune disease with a remarkable immune correlation with the destruction of β cells. Evidence suggests that neutrophil infiltration and the formation of NETs are observed before the onset of T1D ( 75 ). A recent study also found high expression of PAD2 mRNA in islet cells, instead of neutrophils, most likely occurring at an earlier stage before inflammatory infiltration.…”
Section: Pathological Functions Of Pads In the Digestive Systemmentioning
confidence: 99%